Rules and regulations of The United Brothers' Birmingham Benefit Society (London : J.S. Forsaith & Son, Printers (T.U.), 1908)
1908 1908 1900s 18 pages 8 8. In order that no delay may take place in paying the sick members their money, after the visitors have signed the sick list, the sick member shall take or send his sick list to the secretary for an order for what money may be due to him, which order must be taken to the club house for the treasurer to advance the money on Saturdays, between 10 a.m. and 4 p.m., or on meeting nights from 8 p.m. till 10 p.m. Any sick member having a complaint against a visitor and not making the same known to the society shall be fined sixpence for each neglect. N.B.— Each sick member to be furnished with a printed sick list, the visitor to sign the list each day he visits or be fined sixpence for each neglect, the sick list to be brought to the club house every meeting night by a representative of the sick member, or be fined sixpence for each neglect. Visitors to be exempt from fines on Good Friday, Christmas Day, and Bank Holidays. 9. Should any member while on the funds of this society be recommended to go into the country for the benefit of his health, he shall give notice to each of the stewards, and get a certificate from a qualified medical man stating that it will be beneficial to the restoration of his health; and if the stewards feel satisfied they may give the sick member such time as they may think needful. 10. Should any member of this society receive any injury or meet his death by fighting (unless it can be proved it was in self-defence) his wife, heir, or nominee shall not be entitled to any benefits from the funds of this society. 11. If a steward shall have cause to think that a member while on the funds is in any way imposing on the same, he shall directly inform the other stewards, and if they see sufficient reason, they shall suspend his pay till the next meeting night, when they shall bring the same before the society, and if they think that such member is an impostor, they shall have him examined by a surgeon or physician, and if his report confirm his deceit he shall be excluded without appeal. And should any member declare off the funds to avoid being 345/7/2/2